A Study to Assess the Effectiveness of Self Intructional Module on Level of Knowledge Regarding Weaning Among Primi Mothers in Paediatric Units in Private Hospitals of Different States, India - Kurian, Midhu; PH, Livana (Universitas Widya Husada, 2020)
Breast milk is the best and safest food for young babies. It is important that babies should be given extra food as well as breast milk at the right age in sufficient amounts to enable them to grow and stay healthy. Weaning is the process in which an infant’s diet pattern is gradually changed from liquid food like breast milk to solid foods which are supplementary food to the breast milk. These can be added after six months of infant’s life because breast milk alone cannot provide the required amount of nutrients and so cannot sustain the growth of the infant after this age. Hence most important aspect of weaning is the introduction of solid food. At about six months of age, while breast feeding is being continued, addition of other food is essential to prevent growth faltering. Delayed introduction of additional food in an exclusively breast fed infant in malnutrition. Improper introduction of foods is fraught with dangers of diarrhea due to infection from unhygienic preparation. Malnutrition related to inadequate calorie intake due to low frequency of feeding and low calorie density of additional foods. Weaning should provide a pleasant experience, not a conflict for mothers and infants. Praise, loving attention, and cuddling are vital to successful weaning. A study was done to assess the effectiveness of self-instructional module on level of knowledge regarding weaning among primi mothers in Paediatric units in a private hospitals with the objectives to assess the level of knowledge among primi mothers regarding weaning before and after self-instructional module, to determine the effectiveness of SIM on weaning and to find out the association between knowledge score with their selected demographic variables. The nature of study was pre experimental. The study was conducted in pediatric units in Private Hospital, Dehradun. The conceptual framework used for this study is based on health belief model. The research design used for this study was one group pre-test post- test design. Data collected using non- probability sampling. The data was collected to assess the effectiveness of 40 primi mothers regarding weaning by level of knowledge score. Pretest analysis revealed that 67.5% primi mothers had inadequate knowledge, 32.5% primi mothers had moderate knowledge. Post test analysis revealed that 65% had adequate knowledge, 35% primi mothers had moderate knowledge.Keywords - Knowledge, Effectiveness, SIM, Weaning, Primi mothers.